2022
DOI: 10.3389/fcomp.2022.924954
|View full text |Cite
|
Sign up to set email alerts
|

Investigating (re)current state-of-the-art in human activity recognition datasets

Abstract: Many human activities consist of physical gestures that tend to be performed in certain sequences. Wearable inertial sensor data have as a consequence been employed to automatically detect human activities, lately predominantly with deep learning methods. This article focuses on the necessity of recurrent layers—more specifically Long Short-Term Memory (LSTM) layers—in common Deep Learning architectures for Human Activity Recognition (HAR). Our experimental pipeline investigates the effects of employing none, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…According to Bock et al [106] we distinguish between sporadic, simple/periodical, transitional, and complex activities. However, datasets shown in Table 1 mostly focus on locomotion activities and activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Bock et al [106] we distinguish between sporadic, simple/periodical, transitional, and complex activities. However, datasets shown in Table 1 mostly focus on locomotion activities and activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…However, datasets shown in Table 1 mostly focus on locomotion activities and activities of daily living. Only a few, such as [26,27,35,51], include sporadic, transition or complex activities, and many datasets that do include sports [16,33] aggregate an entire sport into a single activity. Published sports studies tend to not release their datasets publicly or only upon request-with Trost et al [17] and Bock et al [51] as the only exceptions, as shown in Tables 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations